Youth Experiences of Violence at Home, School, and Street in Disadvantaged Urban Neighborhoods of Islamabad, Pakistan: Troika of Violence. Issue 6 (3rd June 2022) - Shah, Rahat; Hayat, Asif; Zaman, Muhammad; Sabir, Imran
ABSTRACT: Youth and Violence have mostly been correlated with either neighborhood, school, or street environment. The current study aims at exploring how the violent experiences of youth at home, school and the street are interconnected, an area of study that has been overlooked in previous studies. Thirty in-depth interviews were conducted with violent youth aged between 14 and 21 years in two disadvantaged urban neighborhoods of Islamabad. The findings show that youth had cyclical experience of violence on three fronts including their homes, schools, and streets in Islamabad. The analysis led us to term these consequential violent experiences among Pakistani youth as the "Troika" of violence. The troika of violence, thus, engages an individual in its vicious cycle, where shared standards of street code become desirable attributes for the youth of disadvantaged neighborhood at home, school, and the street.